The Pengaruh Pengelolaan Aset Desa, Optimalisasi Pemanfaatan Badan Usaha Milik Desa (Bumdes), dan Profesionalisme Aparatur Desa Terhadap Peningkatan Pendapatan Desa - Handayani, Resty Ditha; Nugraha, Arie Apriadi (Indonesian Accounting Research Journal, 2023)
The objective of this research is to gather empirical evidence on the impact of village asset management, optimizing the utilization of Village Owned Enterprises (BUMDes), and the professionalism of village officials on the increase of village income. The study population consists of the Village Government in Parongpong District, comprising a total of seven villages. The sampling technique employed is saturated sampling, where all villages were included in the study. Primary data was collected through the use of a questionnaire. A sample size of 35 respondents was selected using saturated sampling, covering the entire population. The research methodology adopted is descriptive statistics with a quantitative approach. The data analysis results indicate that the professionalism of village officials has a positive but not statistically significant impact on increasing village income. On the other hand, managing village assets and optimizing the utilization of village-owned enterprises (BUMDes) have a positive and statistically significant impact on increasing village income.